Vaccination against pancreas disease in Atlantic salmon, Salmo salar L., reduces shedding of salmonid alphavirus. (December 2016) - Skjold, Pål; Sommerset, Ingunn; Frost, Petter; Villoing, Stephane
Abstract Salmon pancreas disease virus, often referred to as salmonid alphavirus (SAV), causes pancreas disease (PD) in European salmonids. SAV transmits horizontally from fish shedding virus into the water and ocean currents are believed to be a main contributor of viral spread between marine farms. Vaccination against PD is previously shown to reduce mortality and severity of clinical PD. In this study, we demonstrate that vaccination against PD significantly reduces viral shedding from infected individuals. The results suggest that PD vaccination can be an important tool to reduce the infection pressure, a known key risk for PD outbreaks at neighbouring farms.